Gene expression as a digital communication system - Cevallos Vilacrés, Yesenia Elizabeth; Pantano, Pietro; Marano, Salvatore (My University, 2018)
This PhD thesis extends upon the information theories of digital communication systems to analyse biological communications (nanocommunications) in order to accurately model biological communication as digital communication by providing an essential analysis of the analogies between both systems. As such, this work analysed gene expression from two perspectives: digital communication systems as a general perspective and internetwork systems as a specific perspective (keeping in mind that digital communication networks are a subarea of digital communication systems). First, this work presents a novel layered network model that represents gene expression and the role of the Golgi apparatus as an internetwork router to transmit proteins to a target organ. Second, supported by the aforementioned layered network model, this work presents a digital communication system end-to-end model that represents gene expression with regard to the production of proteinaceous hormones in the endocrine system by using Shannon’s theorem. In addition, each molecular process encoding biological information, from the transcription and translation of deoxyribonucleic acid (DNA) to hormone signalling, is represented by a layered network model. These models apply the general advantages of digital internetworks and systems (i.e., performance and efficiency) to the transmission of biological information in gene expression systems. The proposed models and analysis define the duality between digital and biological communication systems, and the results herein can be used to overcome the disadvantages of both systems. One of the most important applications of the current study is the potential use of the characteristics of both communication systems in the nano/bio-hybrid medical field (i.e., for the treatment of diseases such as cancer). Hence, the analysis presented in this study may prevent side effects by specifically enhancing the transmission of information to a suitable destination (i.e., to specific target organs), thereby facilitating the development of optimal and less expensive treatments.
Dottorato di Ricerca "Archimede" in Scienze, Comunicazione e Tecnologie Indirizzo in: Scienze e tecnologie dei sistemi complessi
Keywords: Gene expression; Digital communications